Broadband ultrafast nonlinear absorption and nonlinear refraction of layered molybdenum dichalcogenide semiconductors - BLAU, WERNER; COLEMAN, JONATHAN; BLAU, WERNER; COLEMAN, JONATHAN NESBIT (My University, 2014)
A series of layered molybdenum dichalcogenides, i.e. ,MoX 2 (X ¼ S, Se and Te), were prepared in cyclohexyl pyrrolidinone by a liquid-phase exfoliation technique. The high quality of the two-dimensional nanostructures was veri fi ed by transmission electron microscopy and absorption spectroscopy. Open- and closed-aperture Z -scans were employed to study the nonlinear absorption and nonlinear refraction of the MoX 2 dispersions, respectively. All the three-layered nano- structures exhibit prominent ultrafast saturable absorption (SA) for both femtosecond (fs) and picosecond (ps) laser pulses over a broad wavelength range from the visible to the near infrared. While the dispersions treated with low-speed centrifugation (1500 rpm) have an SA response, and the MoS 2 and MoSe 2 dispersions after higher speed centrifugation (10 000 rpm) possess two-photon absorption for fs pulses at 1030 nm, which is due to the signi fi cant reduction of the average thickness of the nanosheets; hence, the broadening of band gap. In addition, all dispersions show obvious nonlinear self-defo- cusing for ps pulses at both 1064 nm and 532 nm, resulting from the thermally-induced nonlinear refractive index. The versatile ultrafast nonlinear properties imply a huge potential of the layered MoX 2 semiconductors in the development of nanophotonic devices, such as mode-lockers, optical limiters, optical switches, etc
PUBLISHED
Keywords: nanophotonic devices; nanophotonic devices